Volatility Asymmetry of Scale Indexes - Taking China as an Example - Wei, Shih-Yung; Cheng, Jao-Hong; Lin, Li-Wei; Gan, Su-Mei (International Journal of Economics and Financial Issues, 2020)
This study focused on the volatility asymmetry of scale indexes in China’s stock market. A total of 12 indexes in four categories were studied during the study period, which lasted from January 1, 2012 to September 30, 2018. The study results showed that large-scale volatility asymmetry almost never occurred but small-scale volatility asymmetry was very significant, which could result from the status of information reception in China. It was easier for large companies to receive information than small companies; therefore, compared with small companies, information asymmetry rarely happened to large companies, leading to the situation where small companies were more likely to have fiercer negative responses to information. However, this study did not divide the study period into bull markets and bear markets, and the addition and subtraction of these two periods could dilute the causes of the disappearance of large-scale volatility asymmetry. Keywords: Volatility asymmetry; Scale indexes; EGARCH JEL Classification: G2 DOI: https://doi.org/10.32479/ijefi.8200